Systematic review assessing the evidence for the use of stem cells in fracture healing. (1st October 2020) - Mott, Andrew; Mitchell, Alex; McDaid, Catriona; Harden, Melissa; Grupping, Rachael; Dean, Alexandra; Byrne, Ailish; Doherty, Laura; Sharma, Hemant
Abstract : Aims: Bone demonstrates good healing capacity, with a variety of strategies being utilized to enhance this healing. One potential strategy that has been suggested is the use of stem cells to accelerate healing. Methods: The following databases were searched: MEDLINE, CENTRAL, EMBASE, Cochrane Database of Systematic Reviews, WHO-ICTRP, ClinicalTrials.gov, as well as reference checking of included studies. The inclusion criteria for the study were: population (any adults who have sustained a fracture, not including those with pre-existing bone defects); intervention (use of stem cells from any source in the fracture site by any mechanism); and control (fracture healing without the use of stem cells). Studies without a comparator were also included. The outcome was any reported outcomes. The study design was randomized controlled trials, non-randomized or observational studies, and case series. Results: In all, 94 eligible studies were identified. The clinical and methodological aspects of the studies were too heterogeneous for a meta-analysis to be undertaken. A narrative synthesis examined study characteristics, stem cell methods (source, aspiration, concentration, and application) and outcomes. Conclusion: Insufficient high-quality evidence is available to determine the efficacy of stem cells for fracture healing. The studies were heterogeneous in population, methods, and outcomes. Work to address these issues and establish standards for future research should be undertaken. Cite this article: Bone Joint Open 2020;1-10:628–638.